HOW SOCIAL MEDIA ENHANCES STEM LEARNING: A SYSTEMATIC REVIEW OF IMPLEMENTATION STRATEGIES AND OUTCOMES (2020–2025) - Asmaningrum, Henie Poerwandar; Chien Tiew Mee; Law Hui Nong (International Journal of Instructions and Language Studies, 2026)
This systematic literature review examines social media implementation strategies and learning outcomes in STEM education through analysis of 133 empirical studies published between 2020 and 2025, sourced exclusively from the Web of Science database following PRISMA 2020 guidelines. From an initial pool of 1,810 records, 100 duplicates were removed, and subsequent title-abstract screening, full-text eligibility assessment, and inclusion criteria evaluation yielded the final sample of 133 studies. Studies were systematically categorized by platform type, STEM discipline, and educational level. Among the analytical approaches employed across included studies, social network analysis was most frequently used (30.8%); among social media platforms, YouTube-based implementations were most prevalent (18.8%). Mathematics education showed the strongest disciplinary representation (24.8%), with higher education dominating across all platform categories (58.6%). Synthesis of learning outcomes revealed generally positive effects across cognitive, affective, social, and behavioral dimensions. Social outcomes showed the most consistent positive findings, with 78–91% of studies employing each implementation strategy reporting improvements in peer relationships and learning community formation — though this reflects the proportion of studies reporting positive findings rather than a pooled effect estimate. Implementation challenges centered on technical infrastructure limitations, digital literacy disparities, and institutional resistance, while successful implementations required comprehensive institutional support, professional development, and clear pedagogical frameworks. These findings suggest that social media integration can enhance STEM education effectiveness when implemented systematically within supportive contexts, though future research addressing long-term sustainability and cultural diversity remains essential.